Analiza źródeł finansowania rozwoju i innowacji w przedsiębiorstwach województwa podkarpackiego - Sieńko, Barbara (The Analysis of Funding Sources for the Development and Innovations in Enterprises of Podkarpacie Region, 2006)
One of the essential conditions of development and increasing of podkarpackie region competitiveness, in context of Poland's membership in EU as well as process Of globalization, is the creation and improvement in infrastructure of financial support of the widely understood innovations. They are one of basic realization factors of sustainable development - to which all regions of EU should-aim. Financial resources directed on this aim, offer of financial services adapted to expectations of enterprises, and the utilization of the UE funds, are the basic conditions, which have to be fulfilled for leading development in this direction.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 578-585